Observation of full-parameter Jones matrix in bilayer metasurface - Yanjun Bao; Fan Nan; Jiahao Yan; Xianguang Yang; Cheng-Wei Qiu; Baojun Li (Nature Communications, 2022)
The realization of Jones matrix with full eight free parameters is particularly challenging. Here, the authors construct spatially varying Jones matrix with eight free parameters by cascading two-layer metasurfaces and use it for new optical functionalities.